'URF : MAKNA DAN URGENSINYA DALAM HUKUM ISLAM - Supriyanto, Agus (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2013)
This artide explains the meaning and importance of  'urf. Urf is an Arabic Islamic term referring to the custom, or 'knowledge', of a given society. To be recognized in an Islamic society, Urf must be compatible with the Islamic law. When applied, it can lead to the. deprecation or inoperabiVity of a certain aspect of Islamic Jurisprudents (fiqh) 'Urf is a source of rulings where there are not explicit primary texts of the Qur'an and Tradistion of Muhammad (Sunnah) specifying the ruling. 'Urf can also spedfy something generally established in the primary texts. Urf was first recognized by Abu Yusuf (d. 182/798), an early leader of the Hanafi school. But it was considered part of the sunnah, and not as formal source. This article proposed and explained the ?urf and its application in Islamic law, particularly under the differences among ?urf, 'adah, and ijma' (consensus of jurists). Moreover, the classifications of 'urf were well analysis in the concept af Shari'ah